Fear of Missing Out sebagai Mediasi pada Social Media Marketing terhadap Keputusan Pembelian - Putu Ayu Titha Paramita Pika; Said Agil Harris; Ni Ketut Anjani; Made Mulyadi (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2026)
Customers' purchasing decisions have been altered by the growing intensity of social media use, especially among Generation Z, who are very sensitive to social cues and digital trends. Fear of Missing Out (FOMO) is one psychological phenomena that arises from this setting and may have an impact on consumer behavior beyond logical considerations. The purpose of this study is to examine how social media marketing influences Generation Z customers' purchasing decisions in Denpasar, Indonesia, using FOMO as a mediating variable. A survey with 130 respondents chosen by purposive sampling was used in a quantitative manner. Partial Least Squares-Structural Equation Modeling (PLS-SEM) was used to examine the data. The findings show that FOMO and purchasing decisions are positively and significantly impacted by social media marketing. Furthermore, FOMO significantly influences purchase decisions and partially mediates the relationship between Social Media Marketing and purchase decisions. These findings highlight that effective social media marketing not only relies on engaging content but also triggers emotional and psychological responses that strengthen consumers’ purchasing tendencies. The study provides practical insights for marketers in designing emotionally driven social media strategies targeted at Generation Z.